2021
DOI: 10.1093/plphys/kiab386
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur deficiency-induced genes affect seed protein accumulation and composition under sulfate deprivation

Abstract: Sulfur Deficiency Induced proteins SDI1 and SDI2 play a fundamental role in sulfur homeostasis under sulfate-deprived conditions (-S) by down-regulating glucosinolates. Here, we identified that besides glucosinolate regulation under –S, SDI1 down-regulates another sulfur pool, the S-rich 2S seed storage proteins in Arabidopsis (Arabidopsis thaliana) seeds. We identified that MYB28 directly regulates 2S seed storage proteins by binding to the At2S4 promoter. We also showed that SDI1 down-regulates 2S seed stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…It was also noted that MYB28 directly regulates the 2S SSPs by binding to the At2S4 promoter. In this extension, SDI1 directly downregulates the 2S SSPs by forming a ternary protein complex with MYB28 and MYC2 (another transcription factor regulates the SSPs) [ 70 ]. These findings will help a lot in the future to understand plant responses towards sulfur deficiency.…”
Section: Sulphur Containing Seed Storage Proteins (Ssps)mentioning
confidence: 99%
“…It was also noted that MYB28 directly regulates the 2S SSPs by binding to the At2S4 promoter. In this extension, SDI1 directly downregulates the 2S SSPs by forming a ternary protein complex with MYB28 and MYC2 (another transcription factor regulates the SSPs) [ 70 ]. These findings will help a lot in the future to understand plant responses towards sulfur deficiency.…”
Section: Sulphur Containing Seed Storage Proteins (Ssps)mentioning
confidence: 99%
“…Notably, specific TFs from the HB, MYB and WRKY families are regulated by sulfur deficiency in Arabidopsis: HAT14 (HB family), MYB31, MYB45, MYB52, MYB53, MYB54, MYB71, MYB75/PAP1, MYB93 and WRKY56 are upregulated, while MYB29 and MYB76 are downregulated by –S (Aarabi et al., 2020; Bielecka et al., 2015). Furthermore, because of the presence of a RY cis ‐element in the SDI1 promoter (Figure 1a; Table 1) and the significance of links between OAS and sulfur regulation of seed storage‐protein composition (Kim et al., 1999), major TFs from the B3 family, namely FUS3, ABI3, LEC1 and LEC2, which are involved in the regulation of seed storage‐protein gene expression in Arabidopsis (Aarabi et al., 2021; Luerssen et al., 1998; Stone et al., 2001), may be relevant to SDI expression.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings for SDI1 demonstrated that besides inhibition of GSL biosynthesis, it down-regulates, developmentally or in response to sulfate deprivation, the biosynthesis of sulfur-rich 2S seed storage proteins in Arabidopsis seeds. SDI1 forms a protein complex with MYB28 and MYC2, which binds, for example, to the At2S4 gene promoter ( Aarabi et al , 2021 ). It can be speculated that GSL inhibition is an acquired feature in Brassicaceae , while its control of seed protein composition is a feature of all seed plants.…”
Section: The Downstream Function Of Oas Cluster Genesmentioning
confidence: 99%
“…MYB TFs are known to be involved in numerous plant regulatory processes ( Dubos et al , 2010 ). With respect to sulfur metabolism they have been identified to be involved in GSL biosynthesis regulation ( Celenza et al , 2005 ; Gigolashvili et al , 2007a ; Frerigmann and Gigolashvili, 2014 ; Frerigmann et al , 2014 ; Aarabi et al , 2016 , 2020 ) and in seed storage protein regulation ( Aarabi et al , 2021 ). In the Plant Regulomics database two new MYB TFs have been identified ( Table 3 ) which deserve further analysis.…”
Section: How Are Oas-responsive Genes Regulated?mentioning
confidence: 99%